2004
DOI: 10.1038/sj.bjc.6601472
|View full text |Cite
|
Sign up to set email alerts
|

Area under the curve of methotrexate and creatinine clearance are outcome-determining factors in primary CNS lymphomas

Abstract: Although high-dose methotrexate (HD-MTX) is the most effective drug against primary CNS lymphomas (PCNSL), outcomedetermining variables related to its administration schedule have not been defined. The impact on toxicity and outcome of the area under the curve (AUC MTX ), dose intensity (DI MTX ) and infusion rate (IR MTX ) of MTX and plasmatic creatinine clearance (CL crea ) was investigated in a retrospective series of 45 PCNSL patients treated with three different HD-MTX-based combinations. Anticonvulsants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
85
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 21 publications
3
85
2
1
Order By: Relevance
“…More recently, Blasco and colleagues showed that patients with PCNSL who were early non-responders to chemotherapy (n ¼ 12) had a poorer progression-free survival and OS compared to patients who received three cycles of MBVP (HDMTX, methylprednisolone, etoposide, BCNU) combined with radiotherapy as planned (n ¼ 25) [1]. The mean AUC-MTX in the latter study was 1076 mmol*h/L per 3-week cycle, higher than that found in previous studies (731 mmol*h/L [2] and 931 mmol*h/ L [3]). Although these patients had a fairly good drug exposure on average, some of them were nonresponders, suggesting an unfavorable tumor biology in the latter.…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…More recently, Blasco and colleagues showed that patients with PCNSL who were early non-responders to chemotherapy (n ¼ 12) had a poorer progression-free survival and OS compared to patients who received three cycles of MBVP (HDMTX, methylprednisolone, etoposide, BCNU) combined with radiotherapy as planned (n ¼ 25) [1]. The mean AUC-MTX in the latter study was 1076 mmol*h/L per 3-week cycle, higher than that found in previous studies (731 mmol*h/L [2] and 931 mmol*h/ L [3]). Although these patients had a fairly good drug exposure on average, some of them were nonresponders, suggesting an unfavorable tumor biology in the latter.…”
contrasting
confidence: 53%
“…Methotrexate at doses of roughly 3 g/m 2 (high-dose methotrexate; HDMTX) is the most active and widely used drug against PCNSL. HDMTX is also the single anticancer drug in adult oncology whereby therapeutic drug monitoring (TDM) is routinely performed, primarily to guide leucovorin rescue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Doses less than 3 g/m 2 are probably too low to reach sufficient concentrations in the CSF to kill lymphoma cells [28,29]. A dose of 8 g/m 2 MTX was frequently associated with the need for a dose reduction during the course of the treatment, mostly due to renal toxicity [30,31].…”
Section: Methotrexate Alone or In Combinationmentioning
confidence: 99%
“…MTX inhibits dyhidrofolate reductase, an enzyme that participates in the tetrahydrofolate synthesis. Drug levels over 1 g/m 2 safely penetrates the brain parenchyma, and levels over 3 g/m 2 lead to adequate concentration in the CSF [17][18][19] . For this reason, it has been proposed that in patients receiving 3 g/m 2 or more, intrathecal chemotherapy could be used more cautiously 20 .…”
Section: Treatment Of Primary Cns Lymphoma Is Different From Systemicmentioning
confidence: 99%